MALAY CULTURE ASSIMILATION ON MUSLIM MALABARI COMMUNITIES IN MALAYSIA - Moiden, Abdul Hamid; Liaw, Jessica Ong Hai (The journal of contemporary issues in business and government, 2021)
The Malabari community is a Muslim minority in Malaysia. People from Kerala in India has been living in Malaya since the days of the Malacca Sultanate. One theory of the spread of Islam to Malaya connected with minority communities that of the Shafi‟i sect. Majority of the community presently lives in the states of Johore, Selangor, Perak, Malacca and Penang. The study‟s focus was to examine the assimilation of Malay culture in the life of Muslim Malabaris by looking at the social and cultural aspects that included the assimilation of language communication, education, traditional dress, and wedding. This research was a “non-experimental” study that concentrated on field studies and interviews. Study data were collected through interviews and surveys. The outcomes revealed that the language of the Muslim Malabari community is losing their identity in Malaysia. They already assimilate the Malay culture in their daily lives. This paper also presented some ideas to maintain their identity in Malaysia and recommended further documentation and research to preserve and uphold their customs and traditions not to stay relevant.